REVIEW ARTIKEL PENGARUH VARIASI KOSOLVEN TERHADAP STABILITAS SIRUP PARACETAMOL - Fatimi, Hana Anisa; Manurung, Devi Yanthre Sari; Larasati, Rizky Dwi; Ramadhana, Irma Hazira Awalinda; Putranti, Inneke Nurul Dwi; Kholifatuzzahroh; Shafwa, Mayra (JIFI (Jurnal Ilmiah Farmasi Imelda), 2024)
The syrup is made with the aim of increasing patient acceptance in taking medicine because it is convenient and practical when consumed. Paracetamol is classified as a drug that is rather difficult to dissolve in water with a water solubility of 1: 70 so that in the formulation of syrups it is necessary to assist the dissolution process with several methods such as cosolvention and the addition of surfactants. This review article aims to analyze the studies that have been conducted related to the effect of cosolvent variations on the stability of paracetamol syrup preparation formulations. Several tests were conducted to evaluate the preparation of paracetamol syrup, namely organoleptic test, content determination test, pH test, viscosity test, and specific gravity test. Data was obtained from relevant literature sources such as Google Scholar, ResearchgateNet and Science direct and obtained 10 journals that met the criteria. The use of different cosolvents in syrup will produce different physical values. Paracetamol syrup with PEG 400 and glycerin cosolvents had greater viscosity than paracetamol syrup with propylene glycol and Ryoto sugar ester cosolvents. Paracetamol syrup with PEG 400 and glycerin cosolvents had a greater specific gravity than paracetamol syrup with propylene glycol cosolvents and Ryoto sugar ester surfactant. Based on the results of a review of 10 journal articles, it appears that the use of different cosolvents in paracetamol syrup preparations can modify the preparation and affect the level of stability of the resulting syrup preparation.